(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
This article offers a systematic explanation of the usage of the virtual focus group approach in research, frequently employed to gain an in-depth grasp of the nuances of a given phenomenon. How to focus group approach utilization is suitable pros and cons, and data analysis. An application from Brazilian IT faces some challenges in the virtual environment. Finally, the relevance of employing focus groups is discussed, along with a justification for their broader use in qualitative research.